2022
DOI: 10.3390/ijerph19031039
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Multidrug-Resistant Gram-Negative Bacteria Carriage upon Admission to the Intensive Care Unit

Abstract: Multidrug-resistant Gram-negative bacteria (MDR-GNB) are microorganisms that have acquired resistance to extended-spectrum antibacterials and constitute an emerging threat to public health. Although carriers are an important source of transmission in healthcare settings, data about risk factors for MDR-GNB carriage are limited. Therefore, we aimed to identify risk factors for MDR-GNB carriage upon intensive care unit (ICU) admission and to optimise screening strategies. We conducted a case–control study. Admis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…A limitation of our study include the inability to capture other possible risk factors such as the length of stay in the health facility, previous antibiotic uptake and clinical history. Previous studies have reported them as risk factors associated with the infection by multidrug-resistant organisms in developed and developing countries 72 74 . However, due to the non-availability of such data, we were unable to investigate them in our context.…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of our study include the inability to capture other possible risk factors such as the length of stay in the health facility, previous antibiotic uptake and clinical history. Previous studies have reported them as risk factors associated with the infection by multidrug-resistant organisms in developed and developing countries 72 74 . However, due to the non-availability of such data, we were unable to investigate them in our context.…”
Section: Discussionmentioning
confidence: 99%
“…Multidrug resistance (MDR) in bacterial pathogens is regarded as a global health challenge and represents a serious problem for public health leading to high mortality in human [ 1 4 ]. Globalization, overuse of antibiotics, and self-medication are the most responsible factors spreading antibiotic resistance [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the individual level, patients with antimicrobial-resistant Gram-negative pneumonia are more likely to have been treated previously with antibiotics, be bed-bound, have longer lengths of hospitalisation, have a previous microbiology history of resistant organisms, and to have certain acute and chronic medical comorbidities, with variation by hospital case-mix and region [16,[24][25][26][27][28][29]. Understanding the risk factors for infection with antibiotic-resistant organisms is crucial for effective empiric treatment decision making.…”
Section: Gcrmentioning
confidence: 99%